Identifying available addictive disorder screening tests validated in primary care: A systematic review. (March 2022) - Pautrat, Maxime; Pierre Lebeau, Jean; Laporte, Catherine
Highlights: Seventeen addiction screening tests have been validated in primary care. None of these tests screen for non-substance addictions. Test feasibility and acceptability evaluation in daily practice is required. These tests could facilitate a global approach to addiction. A transversal, comprehensive screening test is required for primary care. Abstract: Background: Substance use disorders and non-substance addictive behaviors are major, growing health concerns. Efficient screening primary care settings encouraged but its widespread implementation is restricted without an appropriate screening approach for clinical practice or guidance for practitioners choose an appropriate screening test. This study aims to identify addictive disorder screening tests which are validated in primary care and suggest steps to help practitioners select the appropriate test. Method: A systematic review of the literature through Pubmed, PsycINFO and The Cochrane Library was performed from database inception to December 21, 2020. The search strategy included three research topics: screening, addictive disorders, and primary care. Selection criteria included published studies evaluating the validity of an addictive disorder screening test in primary care settings. Results: 8638 papers were selected, and 50 studies were included. Seventeen questionnaires validated in primary care covered the main substance use disorders, but none screened for non-substance addictive behaviors. Tests such as ASSIST, S2BI, SUBS and TAPS screen for a variety of substance use disorders while others such as TICS and CAGE-AID only have a few questions to improve feasibility. However, some shorter tests had weaker psychometric properties. Conclusions: Seventeen addictive disorder screening tests validated in primary care are available. The feasibility and acceptability in primary care of the shorter tests needs to be assessed. A transversal screening test, adapted to the constraints of primary care, that enables clinicians to detect substance use disorders and non-substance addictive behaviors is needed.